Increased FIO2 influences SvO2 interpretation and accuracy of Fick-based cardiac output assessment in cardiac surgery patients: A prospective randomized study. Issue 36 (10th September 2021) - Lin, Sheng-Yi; Chang, Feng-Cheng; Lin, Jr-Rung; Chou, An-Hsun; Tsai, Yung-Fong; Liao, Chia-Chih; Tsai, Hsin-I.; Chen, Chun-Yu
Abstract: Introduction: The study aimed to reveal how the fraction of inspired oxygen (FIO2 ) affected the value of mixed venous oxygen saturation (SvO2 ) and the accuracy of Fick-equation-based cardiac output (Fick-CO). Methods: Forty two adult patients who underwent elective cardiac surgery were enrolled and randomly divided into 2 groups: FIO2 < 0.7 or >0.85. Under stable general anesthesia, thermodilution-derived cardiac output (TD-CO), SvO2, venous partial pressure of oxygen, hemoglobin, arterial oxygen saturation, arterial partial pressure of oxygen, and blood pH levels were recorded before surgical incision. Results: Significant differences in FIO2 values were observed between the 2 groups (0.56 ± 0.08 in the <70% group and 0.92 ± 0.03 in the >0.85 group; P < .001). The increasing FIO2 values lead to increases in SvO2, venous partial pressure of oxygen, and arterial partial pressure of oxygen, with little effects on cardiac output and hemoglobin levels. When comparing to TD-CO, the calculated Fick-CO in both groups had moderate Pearson correlations and similar linear regression results. Although the FIO2 <0.7 group presented a less mean bias and a smaller limits of agreement, neither group met the percentage error criteria of <30% in Bland-Altman analysis. Conclusion: Increased FIO2 may influence the interpretation of SvO2 and the exacerbation of Fick-CO estimation, which could affect clinical management. Trial Registration: ClinicalTrials.gov ID number: NCT04265924, retrospectively registered (Date of registration: February 9, 2020).